2014
DOI: 10.1039/c3cc49747j
|View full text |Cite
|
Sign up to set email alerts
|

The taming of oxygen: biocatalytic oxyfunctionalisations

Abstract: The scope and limitations of oxygenases as catalysts for preparative organic synthesis is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
87
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 313 publications
(197 reference statements)
0
87
0
3
Order By: Relevance
“…Oxygenases, which catalyze the addition of oxygen atoms into many organic compounds, show a remarkable enantio- and regio-selectivity and broad substrate specificity [7,8,9,10]. These features make them valuable biocatalysts for the production of synthons relevant for pharmaceutical and chemical industries [4], and it has been suggested that the use of these enzymes will be as prominent as the well-established hydrolases and dehydrogenases [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygenases, which catalyze the addition of oxygen atoms into many organic compounds, show a remarkable enantio- and regio-selectivity and broad substrate specificity [7,8,9,10]. These features make them valuable biocatalysts for the production of synthons relevant for pharmaceutical and chemical industries [4], and it has been suggested that the use of these enzymes will be as prominent as the well-established hydrolases and dehydrogenases [7].…”
Section: Introductionmentioning
confidence: 99%
“…These features make them valuable biocatalysts for the production of synthons relevant for pharmaceutical and chemical industries [4], and it has been suggested that the use of these enzymes will be as prominent as the well-established hydrolases and dehydrogenases [7]. Furthermore, their application in chemical synthesis can replace the use of potentially harmful chemicals (i.e., green chemistry) [8].…”
Section: Introductionmentioning
confidence: 99%
“…A number of other types of enzyme in this class have also been subject to significant interest as biocatalysts because of their ability to functionalise inert C-H bonds. 115,[272][273][274][275] A number of recent reviews have extensively discussed these enzymes both in terms of structural biology and their applications as biocatalysts. 115,116,[275][276][277] This review will discuss how the methods employed to allow the application of some of these enzymes as industrial biocatalysts might be applied to improve the viability of using flavin-dependent halogenases in the same way.…”
Section: Natural Occurrence and Mechanism Of Flavin-dependent Monooxymentioning
confidence: 99%
“…272,275 Reduced flavin co-factors, required by all enzymes of this class, are unstable with respect to oxygen.…”
Section: Flavin-dependent Monooxygenases As Biocatalystsmentioning
confidence: 99%
“…In this context, enzyme catalysis represents a still not fully exploited potential for the development of sustainable and 'greener' chemistry 1 . Oxidoreductases have the capacity to catalyze the introduction and modification of functional groups under mild reactions conditions and belong to the most important biocatalysts 2 . Most redox transformations require the supply of external of cofactors such as NAD(P)H. Methods for cofactor regeneration have been applied in industrial scale.…”
Section: Introductionmentioning
confidence: 99%